Continuing epidural analgesia during the second stage and ACOG definition of arrest of labor on maternal‐fetal outcomes. Issue 8 (14th May 2020) - Zheng, ShengXing; Zheng, Wenwen; Zhu, Tianqi; Lan, Haiyan; Wang, Qian; Sun, Xiao; Hu, MingPin
Abstract : Background: Despite an increase in the rates of epidural labor analgesia, continuation of epidural labor analgesia in the second stage of labor (CEADSSOL) was interrupted by care providers due to fears of increased risk of operative delivery and adverse neonatal outcomes. Therefore, we evaluated the effect of CEADSSOL and the newer American College of Obstetricians and Gynecologists (ACOG) definition of arrest of labor on the length of secondary stage of labor, newborn outcomes, and mode of delivery. Methods: This is a retrospective cohort study. Data collection began during March 2014 and ended in May 2015, 1 year after implementation of both interventions. The primary outcome was the length of secondary stage of labor, mode of delivery and neonatal outcome (Apgar < 7, at 5 minutes). The implementation of continuing epidural analgesia during the second stage of labor was performed with 0.08%‐0.15% ropivacaine and 0.1‐0.2 µg/mL sufentanil. Results: There were a total 10 414 deliveries during the study period. The length of the second stage of labor has no significant differences among groups. The cesarean delivery rate decreased 4.1% (36% vs 40.1%, P  = .0038). Moreover, no significant difference was found in neonatal Apgar scores less than 7 at 5 minutes between two phases. Maternal outcomes remained unchanged. Post‐intervention neonatal parameters including NICU admissions ( P  < .001), incidences of antibiotics usage ( P  < .0001), intubation ( P  = .0003), and 7 days mortality ( P  = .0020) were remarkably reduced compared to pre‐interventions. Conclusion: The important finding of this study was the improvement in neonatal outcomes by implementing two simultaneous interventions without a cost of increased operative delivery.